Cerebral Cystic Echinococcosis - Abolghasem Siyadatpanah; Enrico Brunetti; Amir Emami Zeydi; Yousef Dadi Moghadam; Nelson Iván Agudelo Higuita (Case Reports in Infectious Diseases)
Cystic echinococcosis (CE) is a neglected helminthic disease and major public health problem in several regions of the world. The zoonosis is caused by the larval stage of different cestode species belonging to the genus Echinococcus. CE can affect any organ with the liver and lungs being most commonly involved. The brain is involved in less than 2% of the cases. We report a case of a CE1 echinococcal cyst of the brain in an Iranian patient.